[5, 6]‐Open Methanofullerene Derivatives of Ih‐C801. Issue 45 (18th September 2013) - Izquierdo, Marta; Cerón, Maira R.; Olmstead, Marilyn M.; Balch, Alan L.; Echegoyen, Luis
<x xml:space="preserve">Abstract</x> Newcomers on the scene: The modification of endohedral metallofullerenes with an Ih‐C80 cage by cyclopropanation‐type addition reactions generally yields the [6, 6] methanofullerene adducts. Now [5, 6]‐open methanofullerenes with an Ih‐C80‐derived cage have been synthesized, as confirmed by X‐ray crystallography, under relatively mild, stoichiometric conditions along with the corresponding [6, 6]‐open derivatives in good yields.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>